An integrative review: Challenges and opportunities for stroke survivors and caregivers in hospital to home transition care. (16th July 2020) - Chen, Langduo; Xiao, Lily D.; Chamberlain, Diane
Abstract: Aim: To identify challenges and opportunities for stroke survivors and caregivers in hospital to home transition care. Background: Due to shortened hospital stays, stroke survivors and caregivers must take responsibility for complex care on discharge from hospital to home. Gaps exist in the literature that synthesizes studies on hospital to home transition care. Design: A systematic integrated review. Data sources: Six databases were searched systematically between 18 June 2018 – 31 October 2018 including Medline, CINAHL, Web of Science, ProQuest, Scopus and Science Direct. The search did not have a date limit. Review methods: Studies that met the selection criteria were critically reviewed. Data were extracted from the studies for analyses. A convergent qualitative synthesis approach using inductive thematic synthesis was applied to the review. Results: The analysis of 23 studies identified three major findings. First, health and social care systems influence transition care by either enabling stroke survivors and caregivers to manage transition care via well‐coordinated services or preventing them from accessing services. Second, health professionals' partnership with stroke survivors and caregivers largely decides tailored support for them. Successful partnerships and engagements with stroke survivors and caregivers depend on organizational resources. Third, survivors and caregivers are at different levels of readiness to cope with challenges. Individualized support for them to develop resilience is highly regarded. Conclusion: Stroke survivors and caregivers encounter enormous challenges in self‐management of hospital to home transition care. Further research is required to address their expectations of support during transition care. Impact: There is a lack of synthesis of studies on factors affecting hospital to home transition care for stroke survivors. Health and social care system designs, health professionals' commitment to individualized care and the self‐management capability of stroke survivors and their caregivers have a profound influence on the transition care experiences. Abstract : 目的: 为了确定脑卒中幸存者和护理人员在从医院到家庭的过渡护理中面临的挑战和机遇。 背景: 由于住院时间缩短, 脑卒中幸存者和护理人员必须承担出院回家后的全方位护理责任。有关医院到家庭过渡护理的综合研究文献中存在一些知识空白。 设计: 系统化综合评估。 数据来源: 在2018年6月18日至2018年10月31日期间, 系统地检索了6个数据库, 其中包括医学文献联机数据库、护理学数据库(CINAHL)、科学网(Web of Science)、学位论文全文数据库(ProQuest)、斯高帕斯数据库(Scopus)和科学指引(Science Direct)。检索没有日期限制。 评估方法: 对符合甄选标准的研究进行了严格评估。 从研究中提取数据进行分析。评估时采用了归纳主题综合的收敛定性综合方法。 结果: 通过对23项研究进行分析, 确定了三项主要研究结果。首先, 卫生和社会护理系统对过渡期护理有影响, 使脑卒中幸存者和护理人员能够通过良好协调的服务来管理过渡期护理, 或者阻止他们获得服务。其次, 卫生专业人士与脑卒中幸存者和护理人员的合作关系在很大程度上决定了对他们的个性化支持。与脑卒中幸存者和护理人员的成功合作和接触取决于组织资源。第三, 脑卒中幸存和护理人员应对挑战的准备程度不同。高度重视为他们提供个性化的支持以培养他们的恢复力。 结论: 脑卒中幸存者和护理人员在医院到家庭过渡护理的自我管理方面遇到了巨大的挑战。需要进一步研究解决他们在过渡护理期间对专业人士提供的支持的期望值。 影响: 目前, 缺乏对影响脑卒中幸存者从医院到家庭的过渡护理的因素的综合性研究。卫生和社会护理系统的设计、卫生专业人士对个性化护理的承诺以及脑卒中幸存者及其护理人员的自我管理能力, 都对过渡护理体验产生了深远影响。